1998
DOI: 10.1021/ma980945p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Properties of Thermotropic Polythiophene and Poly(p-phenylene) Derivatives

Abstract: Thermotropic nematic and chiral-nematic conjugated polymers consisting of polythiophene and poly(p-phenylene) backbones carrying cyanobiphenyl and (−)-cholesterol as pendant groups were synthesized and characterized as a new class of optical polymers. Spontaneous assembly of the conjugated backbone was promoted by liquid crystalline mesomorphism on the part of the pendants, thereby allowing uniaxially and helically aligned glassy films to be prepared for polarized photoluminescence (PL) studies. In the thiophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…The following mechanism has been proposed and supported by numerical simulations. [91,92] In each nematic sublayer of the film the lumophores are aligned preferentially parallel to the nematic director. Thus, the light emitted locally by each layer is linearly polarized.…”
Section: Circularly Polarized Electroluminescencementioning
confidence: 99%
See 1 more Smart Citation
“…The following mechanism has been proposed and supported by numerical simulations. [91,92] In each nematic sublayer of the film the lumophores are aligned preferentially parallel to the nematic director. Thus, the light emitted locally by each layer is linearly polarized.…”
Section: Circularly Polarized Electroluminescencementioning
confidence: 99%
“…Following this approach, chiral nematic polythiophene and poly(p-phenylene) derivatives emitted circularly polarized light with absolute values g PL of 0.53 and 0.31 for the PT and PPP derivatives, respectively. [92] Even though this concept proved to be very powerful in CPPL, its direct application to CPEL has not been proven yet. Devices of this type necessarily have to have a thickness of several microns that the CNLC host can display its chiroselective properties.…”
Section: Circularly Polarized Electroluminescencementioning
confidence: 99%
“…The polythiophene family is well known for its environmental stability, melt and solution processability, and versatile synthesis, which allow us to have a significant control over optical and electronic properties [11]. Conjugated polymers with liquid-crystalline (LC) groups in their side chains are currently drawing interest from the viewpoint of multifunctional electrical and optical materials [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In side chain type of LC-conjugated polymer, the main chain can be aligned by virtue of spontaneous orientation of the LC side chain.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the influence of thiophene ring systems on mesomorphic behavior has been the subject of much investigation, and a great number of mesogenic compounds and polymers containing thiophene ring have been synthesized and characterized. [12][13][14][15][16][17][18][19][20][21][22] Cai et al 20,23 reported that the 2,5-thiophene moiety with nonlinear structure is a viable mesogenic core unit, although the liquid-crystalline compounds containing the 2,5-thiophene unit have a narrower mesomorphic temperature range as compared to the liquidcrystalline compounds containing p-phenyene analogues, due to the 32°deviation of the core angle from the linearity. Kossmehl et al also synthesized and investigated a series of liquid-crystalline compounds containing the thiophene ring.…”
Section: Introductionmentioning
confidence: 99%